The Genesis of Insurgency in Northern Mozambique - Matsinhe, David M.; Valoi, Estacio (Institute for Security Studies (ISS), 2019)
Insurgents have attacked towns and villages in Cabo Delgado, the poorest province in Mozambique. The government has responded by sending in the military to stamp out the assailants, using ‘whatever it takes’, amid suspicions that foreign fighters from Tanzania have radicalised local youth who are behind the violence. Other measures to counter the violence include an extra-judicial state of emergency and the suppression of information.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; youth / juventude

Radicalização Islâmica no Norte de Moçambique: O Caso de Mocímboa da Praia - Habibe, Saide; Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2019)
Este artigo analisa o fenómeno da radicalização islâmica no Norte de Moçambique, explorando a complexidade das dinâmicas não só na origem do grupo dos Al-Shabaab como também na estrutura do próprio conflito e violência em Cabo Delgado. Os autores consideram que o fenómeno exige uma pesquisa multidisciplinar aprofundada que tome em conta uma multiplicidade de factores de ordem histórica, social, política, económica e religiosa. Acesso à versão inglesa aqui.
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; poverty / pobreza; youth / juventude

Tanzaniano recruta jovens no Niassa para ataques em Cabo Delgado - Governo de Moçambique (Governo de Moçambique, 2019)
Alguns jovens do distrito de Mecula, no Niassa, norte de Moçambique, são recrutados para integrarem o grupo de malfeitores que protagonizam ataques armados nos distritos do norte da vizinha província de Cabo Delgado.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; GP - Niassa; L - portuguese / português; youth / juventude

Conflict at a Crossroads: Northern Mozambique at a Crossroads - Devermont, Judd; Columbo, Emilia (Northern Mozambique at a Crossroads, 2019)
On October 5, 2017, a group of armed men attacked three police stations in Moçimboa da Praia, starting nearly two years of violence and insecurity that still show no sign of ending. Between the first October incident and August 27, 2019, extremists conducted 173 attacks—79 percent of which were committed against civilians—resulting in over 350 deaths, according to the Armed Conflict Location and Event Database (ACLED).1 There is no consensus on the name or construct of the group committing the violence, but for the purposes of this paper, we will refer to the group as Ahlu Sunnah Wa-Jama (ASWJ), which is one of the several names that observers and local communities have ascribed to the militants.2
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito; youth / juventude

Islamic Insurgency in Cabo Delgado: Extractive Industry, Youth Revolt and Global Terrorism in Northern Mozambique - Bonate, Liazzat J. K. (The University of the West Indies, St Augustine, 2018)
The violent insurgency in northern Mozambican province of Cabo Delgado, that started in October 2017 and is still ongoing, caught the government of the country and the public by surprise. Although this insurgency remains largely unexplored and little understood, the only study done so far has suggested that it is being carried out by Muslim youth connected to Islamic radicalism, in particular to the Harakat alShabaab of Somalia and its offshoots in Kenya, Tanzania, and as far as DRC.1 Islam has a long history in Mozambique, since probably the eighth century.2 According to the 2017 National Population Census, Muslims account for about 18% of the total population the country and 58% of the Cabo Delgado inhabitants. However, Mozambique had never had any visible Islamist radical political movement before.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; youth / juventude

O processo de empoderamento das raparigas em Marrere - Estudo de caso do Projeto Mwarusi - Eloisa Nair Lopes da Costa (Instituto Universitário de Lisboa, 2018)
Desde o Acordo Geral de Paz, assinado em 1992, Moçambique realizou reformas políticas de intervenção no combate à pobreza. Contudo, em 2006, verificou-se que 54% da população moçambicana ainda se encontrava abaixo da linha de pobreza. Foi então que, Moçambique, em parceria com organizações internacionais iniciou os seus esforços na promoção de programas centrados na igualdade e equidade de género e a sua atuação junto de comunidades mais vulneráveis, tendo em conta particularmente a educação e a saúde. Para estes avanços contribuíram os Objetivos de Desenvolvimento do Milénio e o Plano de Ação para a redução da pobreza absoluta. O estudo de caso desenvolvido nesta dissertação tem como objetivo compreender o modo pelo qual o Projeto Mwarusi, implementado pela Girl Move Foundation, contribui para um empoderamento efetivo das raparigas no bairro de Marrere em Nampula, Moçambique, compreender o seu impacto na comunidade e a sua aplicabilidade a outras comunidades e grupos. Para compreender o Projeto Mwarusi e, em particular, a situação da mulher moçambicana e as políticas de promoção de igualdade, equidade e empoderamento existentes em Moçambique, foi necessário realizar-se uma análise multivariada que nos permitiu obter um conhecimento não só teórico, ao nível das perspetivas em questão, como prático que nos deu a oportunidade de conhecer a comunidade, a sua cultura e as suas tradições. Esta investigação tem, então, como objetivo a análise do Projeto Mwarusi, através de uma observação participante ao longo das sessões do projeto, através da realização de entrevistas semiestruturadas e questionários on-line aplicados a seis guias, a oito mentoras do Projeto Mwarusi, o que nos permitirá avaliar o sucesso e impacto do Projeto Mwarusi e, por último, através do acompanhamento do desenvolvimento do projeto entre 2015 e 2018.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; empowerment / empoderamento; gender / género; youth / juventude

Mozambique’s insurgency: a new Boko Haram or youth demanding an end to marginalisation? - Hanlon, Joseph (Africa at LSE, 2018)
Joseph Hanlon argues that Mozambique’s new “Islamic” insurgency is about marginalised youth demanding to be heard, and therefore is similar to anti-establishment protest across the world.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Radicalização Islâmica No Norte De Moçambique: O Caso Da Mocímboa Da Praia - Habibe, Saide; Forquilha, Salvador; Pereira, João (2018)
Contextualização da pesquisa: - No dia 5 de Outubro de 2017, um grupo de homens armados, aparentemente com motivações religiosas, ataca instituições do Estado (postos policiais) na Vila da Mocímboa da Praia; - Rapidamente, o assunto da radicalização islâmica no norte de Moçambique passou a chamar a atenção do Governo, sector privado, sociedade civil, parceiros de cooperação, analistas, comentadores, cidadãos comuns, etc. - Para muita gente, as perguntas comuns eram: De onde vem esse grupo da Mocímboa da Praia? Existe fundamentalismo islâmico em Moçambique? Não são homens da Renamo disfarçados de fundamentalistas islâmicos? - Foi neste contexto que o IESE e o MASC decidiram realizar uma pesquisa exploratória como preparação para uma pesquisa mais aprofundada.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

Vampires, Jihadists and Structural Violence in Mozambique: Reflections on Violent Manifestations of Local Discontent and their Implications for Peacebuilding - Weimer, Bernhard (2018)
This essay seeks to explain, in a historical perspective, recent violent attacks on local institutions and representatives of the Mozambican state. Case studies are taken from three Mozambican Provinces, to which historical cases are added showing similar patterns and targets of armed attacks. Based on desk research , interviews and the review of anthropological and political economy literature, the main causes of local conflicts – all of which with their specific contexts and narratives – are identified as being threefold: Firstly, the historically entrenched political economy dominated by Frelimo deals with discontent and dissent in an authoritariina and often violent way, or, in the words of the anthropologist Bjørn Bertelsen, with ‘warfare as governance’. Secondly, the Limited Access Order firmly established in Mozambique produces socioeconomic exclusion of local social, economic and political stakeholders and interests, notably when it is linked to the extraction of natural resources. A third factor is a ‘now future’ perspective of Mozambican youth, the demographic majority. Caught in ‘waithood’ (Alcinda Honwana), it is alienated from their local communities and cultures, but not absorbed by the society and economy. This makes particlulary male youth vulnerable to global influences, and promises of peers, sometimes associated with radical religious thought and crime networks. The essay further examines the extent to which N-E part of Mozambique with its enormous investments in a Liquified Natural Gas industry is vulnerable to the influence of militant Islam. The study concludes with suggestions to address the local conflicts, emerging at a time, when the long standing ‘warfare’ between the Frelimo Government and Renamo is being negotiated towards a political settlement.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; governance / governação; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

The Evidence Is In: How Should Youth Employment Programs In Low-Income Countries Be Designed? - Fox, Louise; Kaul, Upaasna (Policy Research Working Papers, 2018)
Youth in many low-income countries are entering the labor force in unprecedented numbers, yet many struggle to secure rewarding livelihoods. This paper outlines the economic development challenges that constrain youth's transition into employment, and it parses the evidence on which programs and policies appear to speed that transition. It concludes that it may be time for a fundamental reassessment of approaches for addressing youth employment and the youth transition in low-income countries. Employment opportunities in low-income countries reflect the pace of economic and structural transformation. In designing strategies, policies, and programs to meet the entry-into-employment challenge for youth, the starting point is to diagnose the economy and current/future employment opportunities. Combined with the analysis of youth employment problems from a structural transformation perspective, evidence from rigorous evaluations of youth employment interventions provides new insight into which kinds of interventions are more likely to help youth succeed in certain contexts. The evidence reviewed here casts serious doubt on the efficacy and value of training interventions to help youth enter formal wage employment. The case is stronger for interventions that speed the transition to self-employment in farming or non-farm household enterprises. Support for development of transferable character skills and social integration among youth through positive youth development programs should be tested further for employment and earnings impacts, perhaps along with cash transfers to youth or access to finance. In reviewing the evidence on the cost-effectiveness and sustainability of youth employment impacts, the paper also notes the need for better measures of displacement and general equilibrium effects.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; employment / emprego; youth / juventude

No Niassa, jovens consomem cada vez mais álcool de forma excessiva - Deutsche Welle (DW.COM, 2017)
Na província do norte de Moçambique, muitos adolescentes e jovens entregam-se ao vício por falta de ocupação profissional.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - portuguese / português; employment / emprego; youth / juventude

O papel da educação para a igualdade de género e empoderamento da mulher em Moçambique: o caso da cidade de Lichinga, 2005-2015 - Lucas, Geraldo Cebola João (Revista Litteris, 2015)
Este artigo tem como objecto “o contributo da educação para a equidade de género e empoderamento da mulher em Moçambique: o caso da cidade de Lichinga, 1997-2015”. O terceiro objectivo do milénio defende que para que possa alcançar o desenvolvimento sustentável nos países em vias de desenvolvimento e mesmo os já industrializados é preciso que a questão de género seja tomada como primordial nas políticas e estratégias de desenvolvimento. E tal pressuposto requer, como se defende nos objectivos, uma equidade de género e seu paralelo empoderamento. Porque acredita-se que a questão de género é transversal. É preocupação nesta pesquisa verificar se as políticas de género em Moçambique estão em consonância com o terceiro objectivo do milénio. Em segundo lugar, verificar o grau do cumprimento do terceiro objectivo do Milénio na cidade de Lichinga. A pesquisa é norteada pela seguinte pergunta de pesquisa: “ em que medida as políticas da educação moçambicana têm contribuído para a equidade e empoderamento do género no quadro do terceiro objectivo do milénio?”.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - portuguese / português; education / educação; empowerment / empoderamento; gender / género; youth / juventude

Child Marriage and Adolescent Pregnancy in Mozambique: Policy Brief - Hodges, Anthony (UNFPA, Meninas e Não Noivas, UNICEF, 2015)
Child marriage is one of Mozambique’s most serious but largely ignored development challenges – requiring far greater attention from policy makers Child marriage rates are still very high despite a long-term decline, especially in marriage before the age of 15. Economic pressures and the incentive of bride price appear to be powerful factors driving parents to marry off their daughters at a young age. The high rates of child marriage cannot be allowed to continue without a vigorous response from the government, civil society and development partners.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude